Hormone balance in a climacteric plum fruit and its non-climacteric bud mutant during ripening. (March 2019) - Farcuh, Macarena; Toubiana, David; Sade, Nir; Rivero, Rosa M.; Doron-Faigenboim, Adi; Nambara, Eiji; Sadka, Avi; Blumwald, Eduardo
Highlights: Hormone balance in climacteric and non-climacteric plum fruit revealed a positive relationship between auxin and ethylene. Climacteric and non-climacteric plum fruit showed a positive effect of ethylene in ABA levels during ripening in postharvest storage. Ripening of climacteric and non-climacteric plum fruit are characterized by distinct hormone accumulation pathways and interactions. Abstract: Hormone balance plays a crucial role in the control of fruit ripening. We characterized and compared hormone balance in two Japanese plum cultivars ( Prunus salicina Lindl.), namely Santa Rosa, a climacteric type, and Sweet Miriam, its non-climacteric bud-sport mutant. We assessed hormonal changes in gene expression associated with hormone biosynthesis, perception and signaling during ripening on-the tree and throughout postharvest storage and in response to ethylene treatments. Non-climacteric fruit displayed lower ethylene levels than climacteric fruit at all stages and lower auxin levels during the initiation of ripening on-the-tree and during most of post-harvest storage. Moreover, 1-MCP-induced ethylene decrease also resulted in low auxin contents in Santa Rosa, supporting the role of auxin in climacteric fruit ripening. The differences in auxin contents between Santa Rosa and Sweet Miriam fruit could be the consequence of different routed auxin biosynthesis pathways as indicated by the significant negative correlations between clusters of auxin metabolism-associated genes. Ethylene induced increased ABA levels throughout postharvest storage in both ripening types. Overall, ripening of Santa Rosa and Sweet Miriam fruit are characterized by distinct hormone accumulation pathways and interactions.